Budaya Tri Hita Karana Memoderasi Good Corporate Governance Pada Kinerja Keuangan Lembaga Perkreditan Desa - Latrini, Made Yenni; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi, 2023)
This study aims to determine the effect of Good Corporate Governance (GCG) on Financial Performance and the ability of THK to moderate the effect of GCG on Financial Performance in LPDs in Tabanan Regency, Bali. The agency theory underlies the relationship between principals (krama desa) and agents (LPD managers) in the implementation of GCG in improving their financial performance. The sample used by all LPDs in Tabanan-Bali district from 2016-2019 was determined by the slovin formula. The respondents were the head of the LPD, supervisory agency, and treasurer. Multiple linear regression analysis technique with Moderated Regression Analysis (MRA) is used to determine the direct and moderating effect. The results of the analysis show that the better the application of GCG principles can improve the financial performance of the LPD in Tabanan-Bali district. The application of GCG in an LPD which is strengthened by the application of the THK culture which is used as the basis for its business activities can improve the financial performance of the LPD in Tabanan-Bali district. Keywords: Tri Hita Karana; Good Corporate Governance; Financial Performance; LPD.